PERAN BUKTI AUDIT DALAM PEMBUKTIAN KERUGIAN NEGARA: STUDI YURIDIS NORMATIF - Andre Revalino Agesta,; Veronika Dewi Puspitayani,; Ratna Perwitasari,; Geger Adelia, (Juremi: Jurnal Riset Ekonomi, 2025)
This study aims to analyze the role of audit evidence in proving state losses using a normative legal approach. State losses are a significant legal issue, particularly in the management of state finances. To prove such losses, valid and accountable evidence is required, including audit evidence. This research employs a qualitative method with a normative legal research approach. The findings indicate that audit evidence plays a crucial role in proving state losses, both during investigations and prosecutions. However, challenges remain in the utilization of audit evidence, particularly regarding its admissibility and legality within the criminal justice system